Potential heterogeneous nano-catalyst via integrating hydrothermal carbonization for biodiesel production using waste cooking oil - Abdullah, Rose Fadzilah; Rashid, Umer; Hazmi, Balkis; Ibrahim, Mohd Lokman; Tsubota, Toshiki; A. Alharthi, Fahad (Elsevier, 2021)
Hydrothermal carbonization (HTC) provides alternatives technique to produce a nanosize activated carbon from biomass with a high surface area. Herein, this study we prepared empty fruit bunch-based activated carbon (EFBHAC) using HTC technique. The activated carbon was then functionalized with K2CO3 and Cu(NO3)2 to produce bifunctional nano-catalyst for simultaneous esterification-transesterification of waste cooking oil (WCO). The physicochemical properties were performed i.e. N2 sorptions analysis, TPD-CO2/NH3, FESEM, EDX, FTIR and XRD analysis. The results revealed that produced EFBHAC possessed a BET surface area of 4056.17 m2 g−1, with pore volume of 0.827 cm3 g−1 and 5.42 nm of pore diameter resulting from hydrolysis, dehydration decarboxylation, aromatization and re-condensation during HTC process. Impregnation of EFBHAC with K2CO3 and Cu(NO3)2 granted a high amount of basicity and acidity of 9.21 mmol g−1 and 31.41 mmol g−1, respectively, accountable to high biodiesel yield of 97.1%, produced at the optimum condition of 5 wt% of catalyst loading, 12:1 of methanol to oil molar ratio at 70 °C for 2 h. More than 80% of biodiesel was produced after the 5th cycle depicted the good reusability. The transformations from WCO to biodiesel was confirmed via 1H NMR, FTIR and TGA analysis. Fuel properties revealed kinematic viscosity of 3.3 mm2 s−1, cetane number of 51, flash point of 160.5 °C, cloud and pour point of 11 °C and −3 °C, respectively. These results show the excellent potential of waste materials to prepare bifunctional nano-catalysts to produce higher biodiesel yield which has potential to be commercialized.